1997
DOI: 10.1016/s0038-1098(97)00394-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and X-ray irradiation on CdS-doped glass

Abstract: Photodarkening in semiconductor-doped glass is considered to be due to photoinduced defects. Effects of light and X-ray irradiation on CdS-doped glass have been reported to investigate the nature of photoinduced defects in CdS-doped glass using ESR (electron spin resonance) and luminescence. The photoinduced defects are different from X-ray induced defects and may be located in glass near CdS nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…ESR (electron spin resonance) signal has been observed in X-ray irradiated CdS-doped glass [5]. The X-ray induced signal is proportional to X-ray dose.…”
Section: Resultsmentioning
confidence: 99%
“…ESR (electron spin resonance) signal has been observed in X-ray irradiated CdS-doped glass [5]. The X-ray induced signal is proportional to X-ray dose.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, Hassan et al 1) have reported that bioglass (45% SiO 2 , 24.5% CaO, 24.5% Na 2 O, and 6% P 2 O 5 ) was tenfold more sensitive than commercial alanine dosimeters. In a previous paper, 2) we reported that an ESR signal was observed in X-ray irradiated CdS-doped glass, which contains CdS nanocrystals in silicate glass. CdS nanocrystals act as the source of electrons and holes.…”
mentioning
confidence: 79%
“…Examples of the influence of such factors as pressure, pH of the medium, where the synthesis occurs, X-ray irradiation, high-energy electron irradiation have been investigated [7][8][9][10][11].…”
mentioning
confidence: 99%